PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA PENGIRIMAN LAZADA EXPRESS SAAT HARBOLNAS DI E-COMMERCE - Nugroho, Aji; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2018)
The growth of industry / trade based online has increased significantly. Increased growth is a good impact on other industries, one of which is felt by freight forwarding companies. This research was conducted to examine how the influence of service quality that focus on five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and physical evidence to customer satisfaction of goods delivery service.The sample used in this research is the consumer of Lazada Indonesia in Semarang which has been using the delivery service of Lazada Express during the event harbolnas implemented. Samples taken as many as 100 respondents selected using non probability sampling technique with purposive sampling approach. While the analytical technique used is multiple linear regression analysis including validity test, reliability test, classical assumption test, coefficient of determination, f-test, and t-test.The result of research using SPSS version 21 software aid shows that service quality have positive effect to customer satisfaction. From result of regression coefficient, it is found that tangibles variable (b_5) with coefficient 0,358 has the highest value in giving influence to customer satisfaction. Next the successive variable responsiveness (b_2) with coefficient 0,28; variable empathy (b_4) with coefficient 0,166; variable assurance (b_3) with coefficient 0,164; and variable reliability (b_1) with coefficient 0,153 have influence to customer satisfaction. Hypothesis testing is partially significant independent variables, because all values t count > t table or significance <0.05. Meanwhile, simultaneous hypothesis testing of independent variables is also significant, with the value f count > f table or significance <0.05. Coefficient of determination shows the result that the ability of service quality variables, namely reliability, responsiveness, assurance, empathy, and tangibles in explaining the level of customer satisfaction is 85.9%.